Theoretical study of N2O reduction by CO in Fe-BEA zeolite - Fischer, Gerd; Goursot, Annick; Coq, Bernard; Delahay, Gerard; Pal, Sourav (Chemphyschem, 2006)
Quantum mechanical (QM) and QM/molecular mechanics (MM) studies of the full catalytic cycle of N2O reduction by CO in Fe-BEA zeolite, that is, oxidation of BEA-Fe by NO and reduction of BEA-Fe-alpha O by CO, is presented. A large QM cluster, representing half of the channel of the BEA zeolite, is used. The contribution of the MM embedding to the calculated activation energies is found to be negligible. The minimum-energy paths for N2O decomposition and reduction with CO are calculated using the nudged elastic bond (NEB) method. Calculated band experimental activation energies ore in good agreement The two possible orientations for the gaseous molecules adsorbing on the Fe site that ore found lead to different activation energies.
Keywords: Density functional calculations; iron; nitrogen oxides; reaction mechanisms; zeolites